Obstructive sleep apnoea and right ventricular function: A combined assessment by speckle tracking and three-dimensional echocardiography. (15th September 2017) - Buonauro, Agostino; Galderisi, Maurizio; Santoro, Ciro; Canora, Angelo; Bocchino, Maria Luisa; Lo Iudice, Francesco; Lembo, Maria; Esposito, Roberta; Castaldo, Sabrina; Trimarco, Bruno; Sanduzzi, Alessandro
Abstract: Background: Little is known on right ventricular (RV) involvement in obstructive sleep apnoea (OSA). This study aimed at evaluating early RV dysfunction by standard and advanced echocardiography in OSA. Methods: Fifty-nine OSA patients without heart failure and 29 age-matched controls underwent standard, speckle tracking and real time 3D echocardiography of right ventricle. OSA patients performed lung function tests and overnight cardio-respiratory monitoring with evaluation of apnea-hypopnea index (AHI). Results: OSA had significantly higher body mass index and systolic blood pressure (BP) than controls. RV diameters and systolic pulmonary arterial pressure (sPAP) were significantly higher in OSA, in presence of comparable tricuspid annular plane systolic excursion (TAPSE). OSA showed marginally lower RV global longitudinal strain (GLS) (p < 0.05) and RV lateral wall strain (RV LLS) (p = 0.04). Three-dimensional RV ejection fraction did not differ between the two groups. By stratifying patients according to sPAP, 18 OSA patients with sPAP ≥ 30 mm Hg had lower TAPSE (p < 0.05), RV GLS and RV LLS (both p < 0.001) than 37 patients with normal sPAP. By separate multivariate analyses, RV GLS and RV LLS were independently associated with sPAP (both p < 0.0001), AHI (p = 0.035 and p = 0.015 respectively) and BMI (p < 0.05 and p = 0.034) but not with age and systolic BP in OSA. Conclusions: A subclinical RV dysfunction is detectable by speckle tracking in OSA. The impairment of RV GLS and RV LLS is more prominent than that of TAPSE and is evident when RVEF is still normal. GLS is independently associated with sPAP and OSA severity.